Four new endemic species of Hippeastrum (Amaryllidaceae) from Serra da Canastra, Minas Gerais State, Brazil - Oliveira, Renata Souza De; Semir, João; Dutilh, Julie Henriette Antoinette (Phytotaxa, 2013)
Four new endemic species of Hippeastrum (Amaryllidaceae) from Serra da Canastra (Minas Gerais State, Brazil) are described and illustrated. Hippeastrum canastrense is similar to H. elegans, while H. diniz-cruziae, H. roseoalbum and H. sanfranciscanum are similar to Hippeastrum cipoanum. An identification key for Hippeastrum species from Serra da Canastra is presented. Quatro novas espécies de Hippeastrum (Amaryllidaceae) da Serra da Canastra (Minas Gerais, Brasil) são descritas e ilustradas. Hippeastrum canastrense é similar a H. elegans, enquanto H. diniz-cruziae, H. roseoalbum e H. sanfranciscanum são similares a Hippeastrum cipoanum. Chave de identificação para espécies de Hippeasstrum da Serra da Canastra é apresentada.